Promessa e psicoterapia com adolescente: estudo exploratório acerca da desistência no início de terapia - Vale, Hellen Fonseca de Sousa da Costa (2015)
The purpose of this research is to show and demonstrate how much pay attention at the patient and parents commitment mode is important for the psychoanalytic clinic with teenagers. We start from the main elements that are detected and privileged on the first interviews articulating the theory of speak acts and modal verbs. This dissertation using the clinical method explores the case of four teenagers seen at a school clinic and another teenager attended in a private clinic. At somehow 4 of them given up the process even in the beginning and only one produced the promissory act and continued therapy. It is very important to pay attention to the priorities to be followed throughout the beginning. This study/ research concluded that the inversion of priorities can cause damage and break the promise and consequently the withdrawal of the psychotherapeutic process. Especially when we talk about clinic for teenagers, besides the characteristics of their age it also have interference by parents or guardians. Therefore the issues of understanding concerning the promise in initial meetings it's very important contribute to the understanding and than for the continuity of therapy.